2012
DOI: 10.1007/s10903-012-9661-z
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Prevalence of Herb Usage Among Racial/Ethnic Minorities in the United States

Abstract: Clinical studies display a wide range of herb use prevalence among racial/ethnic minorities in the United States. We searched databases indexing the literature including CINAHL, EMBASE, Global Health, CAB Abstracts, and Medline. We included studies that reported herbal medicine prevalence among ethnic minorities, African American, Hispanic, or Asian adults living in the United States. Data from 108 included studies found the prevalence of herb use by African Americans was 17 % (range 1–46 %); for Hispanics, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
(15 reference statements)
1
22
0
Order By: Relevance
“…This study may have had higher number of participants by distributing surveys that could be taken in Spanish to prevent potential language barriers. This was evidenced by Gardiner et al 9 who found that bilingual studies may allow participants to explain more about their herb use if English is not their primary language. 9 In our study, over half of the respondents (58%) completed the survey in Spanish.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This study may have had higher number of participants by distributing surveys that could be taken in Spanish to prevent potential language barriers. This was evidenced by Gardiner et al 9 who found that bilingual studies may allow participants to explain more about their herb use if English is not their primary language. 9 In our study, over half of the respondents (58%) completed the survey in Spanish.…”
Section: Discussionmentioning
confidence: 97%
“…7,8 It is estimated that approximately 20% of the population of the U.S. use medicinal plants on a regular basis. [9][10][11] In a 2007…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research using the 2002 National Health Interview Survey/Complementary and Alternative Medicine supplement (NHIS-CAM) showed that 20% of the U.S. population used some type of herb or supplement in the last 12 months (Kennedy, Wang, & Wu, 2008). Prevalence among Hispanics and Asians is 30% (Gardiner et al, 2012), and prevalence is higher among women than men (Eisenberg et al, 1998;Mackenzie, Taylor, Bloom, Hufford, & Johnson, 2003).…”
mentioning
confidence: 99%